2006
DOI: 10.1111/j.1365-2672.2006.02922.x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of the adventitious microflora of a smear-ripened cheese

Abstract: Aims:  To determine the relationships between the major organisms from the cheese‐making personnel and environment and the surface of a smear cheese. Methods and Results:  360 yeast and 593 bacteria from the cheese surface, the dairy environment and the hands and arms of personnel were collected. Pulsed‐field gel electrophoresis, repetitive sequence‐based polymerase chain reaction and 16S rDNA sequencing were used for typing and identifying the bacteria, and mitochondrial DNA restriction fragment length polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 42 publications
6
77
1
4
Order By: Relevance
“…An understanding of the specificity of the BFIs that occur on the yeast surface will help industries that commercialize ripening microbial cultures to select the most adapted bacterial strains. Indeed, it was shown that despite massive early inoculations, commercial inocula do not always colonize the cheese surface due to the rapid development of adventitious microbiota originating from the cheese production environment (260). Unraveling the ecology of the multispecies cheese ecosystem may have benefits for food safety as well.…”
Section: Food Processingmentioning
confidence: 99%
“…An understanding of the specificity of the BFIs that occur on the yeast surface will help industries that commercialize ripening microbial cultures to select the most adapted bacterial strains. Indeed, it was shown that despite massive early inoculations, commercial inocula do not always colonize the cheese surface due to the rapid development of adventitious microbiota originating from the cheese production environment (260). Unraveling the ecology of the multispecies cheese ecosystem may have benefits for food safety as well.…”
Section: Food Processingmentioning
confidence: 99%
“…Yeasts and molds may enter cheese from a variety of sources, including the starter culture, ambient air, brine, processing equipment, and workers [5,34,39]. Many yeasts can contribute to taste, flavor, and appearance; however, not all species produce beneficial effects, and a species may benefit one cheese while spoiling another.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the microbial populations involved in fermentation and ripening are often found on the processing surfaces (1,3,5,6), highlighting the importance of the plant environment in potentially contributing to the microbiota of cheese. Depending on the nature of the microorganisms, the environmental microbiota can exert functional activities important for the fermentative and/or the ripening process but sometimes may also be a hazard for cheese quality and safety (7).…”
mentioning
confidence: 99%